How Experiences Affect Psychological Responses During Supervised Fasting: A Preliminary Study - Ma, Qianying; Yang, Chao; Wu, Ruilin; Wu, Manrui; Liu, Wenjun; Dai, Zhongquan; Li, Yinghui (Frontiers in Psychology, 2021)
As an unusual event, fasting can induce strong physiological and psychological reactions, but there is still no clear understanding of how previous fasting experiences affect people’s responses to current fasting. This study aimed to investigate the influence of previous fasting experiences on participants’ basic physiological and psychological responses in a fasting experiment conducted under intensive medical monitoring. For a 22-day experiment divided into four phases (3-day Baseline; 10-day Complete Fasting; 4-day Calorie Restriction; and 5-day Recovery phases), a total of 13 persons participated; the participants were divided into a group with prior fasting experience (Experienced: N = 6) and a group without prior fasting experience (Newbie: N = 7). The results indicate no group differences in physiological responses (i.e., weight, glucose, and ketone bodies); however, differences in psychological states were observed, with the Newbie group showing more negative psychological states overall throughout the experiment (i.e., greater appetite, more negative mood states, more stress, less vitality, and fewer recovery resources). Hence, previous fasting experience may be a buffer against negative feelings during current fasting. For this reason, it is important to consider fasting experiences as a vital factor in future research.